SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN PROGRAM STUDI DI STMIK NEUMANN DENGAN METODE LOGIKA FUZZY TSUKAMOTO - Denny Hasminta S. Maha (Jurnal Teknovasi : Jurnal Teknik dan Inovasi, 2022)
When student candidates want to choose a major in STMIK Neumann, they have difficulties to choose the suitable major for them. Therefore, STMIK Neumaan must assist them by providing a decision support system to help them to make a suitable major. Data used by this decision support system must be taken from their results in enrollment test. The method used by this decision support system is to use Tsukamoto method in Fuzzy Logic. This system can display the result in a program which is suitable criteria by Tsukamoto method. The results of enrollment test is inputted to the system, and sequentially will be processed according the suitable criteria by application using Tsukamoto method. The output will display the suitable major for the student candidatse who take enrollment test in STMIK Neumann.